Penerapan Family Support Dalam Mengatasi Dissapointment Pada Lansia (Studi Kasus Pada Klien “M” Di Desa Cinta Jaya Kecamatan Pedamaran Kabupaten Ogan Komering Ilir) - Indriani, Indriani; Kusnadi , Kusnadi; Noviza, Neni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Elderly (Elderly) is the final phase of a person's life who often looks at the past with regret and ignores the future. This is part of the human growth and development process which involves physical, mental and social changes. Elderly people often experience stress, depression and disappointment. Family support is very important in overcoming this problem. The case study of Client "M" shows that the elderly experience dissapointment, emotions and stress. The Family Support approach is an effective solution, with the aim of understanding, accepting and encouraging individuals. Family support helps increase self-confidence and motivation to face problems. This research examines the application of family support in overcoming dissatisfaction in the elderly (Case Study of Client M in Cinta Jaya Village, Ogan Komering Ilir Regency). The aim is to identify forms of dissatisfaction in client M and analyze the application of family support to overcome this dissatisfaction. The method used is a qualitative approach with case studies and field research. Data was obtained through observation, interviews and documentation, and analyzed using pattern matching, explanation and time series analysis methods. The results show various forms of disappointment in client M, including with themselves, other people, living conditions and the surrounding environment. Implementing family support involves the stages of a counseling approach, problem identification, problem solving strategies, implementation, evaluation, and feedback. The researcher succeeded in helping client "M" change his mindset and accept his condition, as well as strengthen family ties through loving support.